Strengthening the Role of Families in Healthy Lifestyle Changes as a Preventive Effort for Heart Disease Patients in the Working Area of the Kalumpang Community Health Center, Ternate City - Nursia Aja; Ismawanti Sawedi; Diah Ariana; Ratih Sakti Prastiwi (CV. Inara, 2026)
Heart disease is a high-risk cardiovascular disease that occurs due to narrowing or blockage of the coronary arteries by plaque, so that blood flow to the heart is disrupted and can cause chest pain, heart attacks, and sudden death. This study aims to strengthen the role of families in encouraging healthy lifestyle changes as an effort to prevent coronary heart disease in the work area of ​​the Kalumpang Community Health Center. Research Methods: This study used an observational analytical design with a cross-sectional approach to analyze factors related to strengthening the role of families in healthy lifestyle changes as an effort to prevent coronary heart disease in the work area of ​​the Community Health Center. The study population included all heart disease sufferers recorded in the register book at the Kalumpang Community Health Center during 2025. The sampling technique used was total sampling, so that the entire population was used as a research sample. Results: The physical activity variable has an Odds Ratio (OR) value of 12,600, which means that individuals who do not do physical activity have a chance of about 12.6 times greater. Dietary patterns have a significant relationship with the incidence of heart disease, indicated by p value = 0.014 and OR = 4.148, which means that individuals with poor diet have a chance of about 4.1 times greater. Smoking habits have a significant relationship with efforts to prevent heart disease, with p value = 0.018 and OR = 3.838. This means that individuals who have a smoking habit are at risk of about 3.8 times greater. Compliance has a very significant relationship with efforts to prevent heart disease, with p value = 0.000 and OR = 13.964. Family attitudes have a very significant relationship with efforts to prevent heart disease, indicated by p value = 0.000 and OR = 13.444. Conclusion: This study shows that strengthening the role of the family is very important in encouraging healthy lifestyle changes as an effort to prevent heart disease in the working area of ​​the Kalumpang Community Health Center, Ternate City. Compliance, attitude, physical activity, and knowledge are the main factors, while unhealthy behavior and lack of family support increase the risk. Therefore, family-based interventions are needed through education at the Kalumpang Community Health Center, accompanied by counseling, mentoring, policy support, cross-sector collaboration, and increased outreach for heart disease prevention.